2017
DOI: 10.1021/acsami.7b02872
|View full text |Cite
|
Sign up to set email alerts
|

Healable Antifouling Films Composed of Partially Hydrolyzed Poly(2-ethyl-2-oxazoline) and Poly(acrylic acid)

Abstract: Antifouling polymeric films can prevent undesirable adhesion of bacteria but are prone to accidental scratches, leading to a loss of their antifouling functions. To solve this problem, we report the fabrication of healable antifouling polymeric films by layer-by-layer assembly of partially hydrolyzed poly(2-ethyl-2-oxazoline) (PEtOx-EI-7%) and poly(acrylic acid) (PAA) based on hydrogen-bonding interaction as the driving force. The thermally cross-linked (PAA/PEtOx-EI-7%)*100 films show strong resistance to adh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 61 publications
(106 reference statements)
1
41
0
Order By: Relevance
“…Sequential deposition of thiol-containing PEOX/poly(methacrylic acid) multilayers onto silica particle templates and crosslinking yielded stable capsules after removing the silica templates [50]. Sun et al demonstrated that the film prepared with partially hydrolyzed PEOX and PAA shows healable and anti-fouling properties [51].…”
Section: Introductionmentioning
confidence: 99%
“…Sequential deposition of thiol-containing PEOX/poly(methacrylic acid) multilayers onto silica particle templates and crosslinking yielded stable capsules after removing the silica templates [50]. Sun et al demonstrated that the film prepared with partially hydrolyzed PEOX and PAA shows healable and anti-fouling properties [51].…”
Section: Introductionmentioning
confidence: 99%
“…All these merits make polymeric complexes suitable for convenient and cost‐effective fabrication of self‐healing/healable polymeric materials with enhanced mechanical strength. Up to now, most self‐healing/healable polymeric materials based on polymeric complexes are fabricated by layer‐by‐layer assembly method involving alternate deposition of polymers with complementary noncovalent interactions at interface of solid substrates and polymer solutions . Among the few examples of self‐healing/healable polymeric composite materials fabricated with polymeric complexes, they have low mechanical strength with tensile strength of several megapascals and exhibit decreased stability after a long‐term exposure to water .…”
Section: Summary Of Mechanical Properties Of the Paa–pvpon Compositesmentioning
confidence: 99%
“…Several microns-thick PEOXA-EI/PAA multilayers, obtained after thermal crosslinking of pristine LbL assemblies, efficiently resisted contamination by Escherichia coli (E. coli) and Bacillus subtilis (B. subtilis), and additionally featured healable properties when mechanically damaged. [30] The biopassive and pH-responsive properties of very similar LbL coatings deposited on SiO 2 surfaces were investigated in detail by the group of Siew Tan (Figure 3d). Crosslinked PEOXA-EI/PAA multilayered films presented a tunable swollen thickness as a function of pH, while they significantly suppressed surface contamination by BSA (Figure 3e), fibroblasts, E. coli and Staphylococcus aureus (S. aureus).…”
Section: Surface Functionalization Strategiesmentioning
confidence: 99%